2015
DOI: 10.1021/sb5003357
|View full text |Cite
|
Sign up to set email alerts
|

Short Synthetic Terminators for Improved Heterologous Gene Expression in Yeast

Abstract: Terminators play an important role both in completing the transcription process and impacting mRNA half-life. As such, terminators are an important synthetic component considered in applications such as heterologous gene expression and metabolic engineering. Here, we describe a panel of short (35-70 bp) synthetic terminators that can be used for modulating gene expression in yeast. The best of these synthetic terminator resulted in 3.7-fold more fluorescent protein output and 4.4-fold increase in transcript le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
203
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(208 citation statements)
references
References 22 publications
4
203
1
Order By: Relevance
“…Refractory elements in the 3′ untranslated region (UTR) that increase mRNA half-life might be available. In Saccharomyces cerevisiae , several terminator regions have shown activity in increasing the production of proteins by upstream coding genes89101112. Whereas some cis -elements within the 3′-UTR and its corresponding trans proteins downregulate gene expression via mRNA degradation or translational repression1314, in vertebrates a few promote the accumulation of protein through translation initiation by cytoplasmic polyadenylation15, stabilization of fragile mRNA16, or translational activation1718 by formation of mRNA–protein complexes.…”
mentioning
confidence: 99%
“…Refractory elements in the 3′ untranslated region (UTR) that increase mRNA half-life might be available. In Saccharomyces cerevisiae , several terminator regions have shown activity in increasing the production of proteins by upstream coding genes89101112. Whereas some cis -elements within the 3′-UTR and its corresponding trans proteins downregulate gene expression via mRNA degradation or translational repression1314, in vertebrates a few promote the accumulation of protein through translation initiation by cytoplasmic polyadenylation15, stabilization of fragile mRNA16, or translational activation1718 by formation of mRNA–protein complexes.…”
mentioning
confidence: 99%
“…They are the yeast DEG1 [15] (DEG1t) and the synthetic Tsynth8 [16] terminators. The latter, in particular, was chosen since it was described as one of the most efficient, among a collection of 30 synthetic terminators, to block RNA polymerase II read-through between two adjacent transcription units expressing different fluorescent proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This minimal scaffold was both diversified and enhanced using modified consensus termination elements and mRNA stability elements [128] to produce a library of rationally designed synthetic terminators (Fig. 3c) which were functional in multiple hosts and improved CAD1 expression for itaconic acid production [129]. Importantly, this technique allowed delineation of design rules based on consensus element identity and spacing, enabling potential rational design of synthetic terminators.…”
Section: Synthetic Terminator Scaffolds and Librariesmentioning
confidence: 99%
“…In S. cerevisiae, however, terminator function is much less predictable based simply on distinct sequence elements whose function is determined by biophysical models. In fact, characterization of the aforementioned rationally designed synthetic library [129] demonstrated that consensus termination motifs were not entirely additive. This suggests there is a fundamental code underlying termination in yeast which remains to be uncovered before thermodynamic prediction becomes feasible.…”
Section: Thermodynamic Modeling and Prediction Of Terminatorsmentioning
confidence: 99%